Accelerated weathering studies on the bioplastic, poly(3-hydroxybutyrate-co-3-hydroxyvalerate). (April 2016) - Wei, Liqing; McDonald, Armando G.
Abstract: The effect of accelerated weathering exposure time on the bioplastic, poly(3-hydroxybutyrate- co -3-hydroxyvalerate) (PHBV) was studied. The chemical structure and thermophysical property changes of solvent cast PHBV films were examined by a combination of optical microscopy, size exclusion chromatography, FTIR and 1 H NMR spectroscopies, tensile testing, and differential scanning calorimetry (DSC). The exposed PHBV surfaces experienced surface crazing upon weathering. The molar mass of weathered PHBV was shown to decrease due to chain scission which was dominant over the crosslinking reaction mechanism, and compositional analysis showed the polymer degradation was non-random between the hydroxybutyrate-hydroxyvalerate units. The degree of crystallinity for PHBV was shown to increase significantly (by about 20%) upon weathering. Tensile tests showed that the weathered PHBV exhibited reduced ultimate strength and elongation to break, while the Young's modulus increased ascribing to an increase in crystallinity. Different degradation mechanisms (Norrish I/II, radical initiation, crosslinking, and hydrolysis) of PHBV are proposed and confirmed based on the experimental findings. This study provides degradation insight for PHBV exposed to both UV radiation and moisture.